A genome-wide assessment of stages of elevational parapatry in Bornean passerine birds reveals no introgression: implications for processes and patterns of speciation - Moyle, Robert G.; Manthey, Joseph D.; Hosner, Peter A.; Rahman, Mustafa; Lakim, Maklarin; Sheldon, Frederick H. (PeerJ, 2017)
Topographically complex regions often contain the close juxtaposition of closely related species along elevational gradients. The evolutionary causes of these elevational replacements, and thus the origin and maintenance of a large portion of species diversity along elevational gradients, are usually unclear because ecological differentiation along a gradient or secondary contact following allopatric diversification can produce the same pattern. We used reduced representation genomic sequencing to assess genetic relationships and gene flow between three parapatric pairs of closely related songbird taxa (Arachnothera spiderhunters, Chloropsis leafbirds, and Enicurus forktails) along an elevational gradient in Borneo. Each taxon pair presents a different elevational range distribution across the island, yet results were uniform: little or no gene flow was detected in any pairwise comparisons. These results are congruent with an allopatric “species-pump” model for generation of species diversity and elevational parapatry of congeners on Borneo, rather than in situ generation of species by “ecological speciation” along an elevational gradient.
Keywords: Parapatry; Speciation; Species pump; Elevation; Borneo; Elevational cline